Production of hydrocarbon fuels by heterogeneously catalyzed oligomerization of ethylene: Tuning of the product distribution. (November 2022) - Betz, Matthias; Fuchs, Constantin; Zevaco, Thomas A.; Arnold, Ulrich; Sauer, Jörg
Abstract: In the field of gasoline synthesis from renewable resources, highly integrated procedures with a minimum of process steps are mandatory to ensure efficient and sustainable production as well as marketability. In this context, oligomerization of ethylene to gasoline-type hydrocarbons is a viable option. The reaction has been studied employing a nickel silica-alumina catalyst and focusing on the influence of temperature, pressure, space velocity and time on stream on the product spectrum. Temperature and pressure largely influenced selectivity and intramolecular branching. The catalyst showed a stable performance during 170 h at 120 °C, 50 bar ethylene partial pressure and a space velocity of 8 h −1 . Under these conditions, ethylene conversion was steadily beyond 99%. Selectivity to C6, C8, C10 and C12 fractions was 15%, 25%, 18% and 10% while the average content of iso-olefins was 24%, 85%, 94% and 96%, respectively. The product selectivity slightly changed with increasing time on stream leading to less branched oligomers, probably due to slight catalyst deactivation. To evaluate the suitability of the C5-12 fraction for fuel applications, it was hydrogenated and parameters like density, lower heating value, boiling behavior, vapor pressure, viscosity, flashpoint, autoignition temperature and oxidation stability have been determined. Graphical abstract: Dehydration of ethanol followed by oligomerization of the resulting ethylene is a comparatively direct route for the production of hydrocarbon fuels from renewable resources. The latter step has been investigated within this study with a strong focus on the influence of reaction conditions on product compositions. Some fuel characteristics of hydrogenated product fractions have been determined. Image 1 Highlights: Synthesis of hydrocarbon fuels by oligomerization of ethylene studied. Nickel on silica-alumina support as efficient heterogeneous catalyst. Influence of reaction conditions for a 1.9% Ni/SIRALOX catalyst on products disclosed. High pressure and low space velocity favor the formation of di-branched octenes. Long-term study shows no decrease of conversion but slight decrease of branching.